Electroactive haloalkaliphiles exhibit exceptional tolerance to free ammonia. Issue 2 (4th December 2017) - Ledezma, Pablo; Lu, Yang; Freguia, Stefano
Abstract: Electrochemical activity in bacteria has been observed in numerous environments and conditions. However, enrichments in circumneutral freshwater media where acetate is the main electron donor seem to invariably lead to the dominance of Geobacter spp. Here we report on an electroactive bacterial consortium which was enriched on acetate as electron donor, but in a medium which reproduces hydrolysed urine (high pH, high salinity and high free ammonia). The consortium was found to be free of Geobacter species, whereas a previously undescribed community dominated by species closely related to Pseudomonas and Desulfuromonas was established. The salient features of this community were as follows: (i) high electroactivity, with anodic current densities up to 47.4 ± 2.0 A m –2 ; (ii) haloalkaliphilicity, with top performance at a medium pH of 10 and 19.5 ± 0.5 mS cm −1 ; and (iii) a remarkably high tolerance to free ammonia toxicity at over 2200 mgNH3 -N L −1 . This community is likely to find applications in microbial electrochemical technology for nutrient recovery from source-separated urine. Abstract : This work reports on a previously undescribed microbial community, capable of converting organic matter to electricity while thriving in harsh environments characterised by high pH and ammonia, conditions which are generally inhibiting, or even biocidal, to most bacterial communities found in natural or engineered systems.